Insulated wire and method for manufacturing same
By forming a fluororesin layer with melt processability on the conductor of the insulated wire and ensuring its peeling or extraction strength through strength testing, the problem of insufficient strength bonding between the conductor and the fluororesin layer is solved, and higher mechanical strength and stability are achieved.
Patent Information
- Application Number
- CN202380060976.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-25
- Filing Date
- 2023-08-25
- Publication Date
- 2025-04-04
AI Technical Summary
In the conventional insulated wire, the strength of the conductor and the fluororesin layer are insufficient, resulting in the fluororesin layer being easily floated from the conductor or wrinkled when bent or bent.
By forming a fluororesin layer with melt processability on the conductor, and by testing the strength of peeling or extracting the fluororesin layer, it is ensured that the peeling strength between the conductor and the fluororesin layer reaches 0.30 N/mm or above or the extraction strength reaches 4N or above.
The sufficient strength bond between the conductor and the fluororesin layer coated with the conductor is achieved, and the floating and wrinkle of the fluororesin layer is avoided when bending or bending is avoided, and the mechanical strength and stability of the insulated wire are improved.
Smart Images

Figure BDA0005278938150000091 
Figure BDA0005278938150000171 
Figure BDA0005278938150000241
Abstract
Description
Technical Field
[0001] The present disclosure relates to an insulated electric wire and a method for manufacturing the same. Background Art
[0002] Patent document 1 describes an insulated wire having an insulating layer made of fluororesin on a conductor, wherein the insulating layer is subjected to induction heating treatment together with the conductor so that the peel strength of the insulating layer relative to the conductor is greater than 0.05 N / mm.
[0003] Patent Document 2 describes an insulated electric wire in which an oxide film is formed on the surface of a conductor by heating through electrical conduction.
[0004] Patent Document 3 describes an insulated wire which contains a polyetherketoneketone resin as a main component and is produced by heating a conductor under conditions that do not allow the polyetherketoneketone to crystallize.
[0005] Patent Document 4 describes an insulated electric wire which contains polyphenylene sulfide and polyetherketoneketone as main components and in which the conductor is heated at a maximum of 360 degrees by electrical heating.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2009-245857
[0009] Patent Document 2: Japanese Patent Application Publication No. 2014-154511
[0010] Patent Document 3: Japanese Patent Application Publication No. 2015-138626
[0011] Patent Document 4: Japanese Patent Application Publication No. 2014-103045 Summary of the invention
[0012] Problems to be solved by the invention
[0013] An object of the present disclosure is to provide an insulated wire in which a conductor and a fluororesin layer covering the conductor are in close contact with each other with sufficient strength.
[0014] Means for solving problems
[0015] According to the present disclosure, there is provided an insulated wire comprising a conductor and a fluororesin layer formed on the conductor and containing a melt-processable fluororesin, wherein the peel strength measured by peeling the fluororesin layer from the conductor is 0.30 N / mm or more.
[0016] Effects of the Invention
[0017] According to the present disclosure, it is possible to provide an insulated wire in which a conductor and a fluororesin layer covering the conductor are in close contact with each other with sufficient strength. DETAILED DESCRIPTION
[0018] Hereinafter, specific embodiments of the present disclosure will be described in detail, but the present disclosure is not limited to the following embodiments.
[0019] The insulated wire of the present disclosure includes a conductor and a fluororesin layer formed on the conductor and containing a melt-processable fluororesin.
[0020] Fluororesin has non-adhesive properties, so when a fluororesin layer is directly provided on a conductor of an insulated wire, there is a problem that the conductor and the fluororesin layer cannot be closely attached with sufficient strength. Therefore, when the conventional insulated wire is bent or folded, there is a problem that the fluororesin layer floats from the conductor or wrinkles are generated in the fluororesin layer.
[0021] The first insulated wire of the present invention has a peel strength of 0.30 N / mm or more measured by peeling the fluororesin layer from the conductor. Therefore, in the first insulated wire of the present invention, the conductor and the fluororesin layer covering the conductor are in close contact with each other with sufficient strength, the fluororesin layer is not easily lifted from the conductor by bending or folding, and wrinkles are not easily generated in the fluororesin layer.
[0022] The cross-sectional shape of the conductor of the first insulated wire disclosed in the present invention is typically approximately rectangular. The first insulated wire disclosed in the present invention may be a flat wire. In particular, when the cross-sectional shape of the conductor is rectangular, when the insulated wire is bent in the side direction, the fluororesin layer covering the outer peripheral portion of the bend is greatly stretched compared to the fluororesin layer covering the inner peripheral portion of the bend, and the fluororesin layer is easily peeled off from the conductor and floats. In addition, when the insulated wire is bent in the side direction, the fluororesin layer covering the inner peripheral portion of the bend shrinks more than the fluororesin layer covering the outer peripheral portion of the bend, and the fluororesin layer is easily wrinkled. Since the conductor of the first insulated wire disclosed in the present invention is tightly attached to the fluororesin layer covering the conductor with sufficient strength, the fluororesin layer is not easy to float from the conductor even when it is bent in the side direction, and the fluororesin layer is not easy to wrinkle.
[0023] The first insulated wire of the present disclosure preferably has a peel strength of 0.50 N / mm or more, more preferably 1.00 N / mm or more, further preferably 1.70 N / mm or more, and particularly preferably 3.00 N / mm or more. The upper limit of the peel strength is not limited, and may be, for example, 10.00 N / mm.
[0024] The peel strength is the maximum tensile stress measured when the fluororesin layer is peeled off from the conductor in the long axis direction (length direction) over a distance of 30 mm at a rate of 100 mm / min.
[0025] The second insulated wire of the present disclosure has a pull-out strength measured by pulling out the fluororesin from the conductor of 4 N or more. Therefore, in the second insulated wire of the present disclosure, the conductor and the fluororesin layer covering the conductor are in close contact with each other with sufficient strength, the fluororesin layer is unlikely to float from the conductor due to bending or folding, and wrinkles are unlikely to occur in the fluororesin layer.
[0026] The cross-sectional shape of the conductor included in the second insulated wire of the present disclosure is typically approximately circular. The second insulated wire of the present disclosure may be a round wire.
[0027] The first insulated wire of the present disclosure preferably has a pull-out strength of 5 N or more, more preferably 6 N or more, further preferably 12 N or more, and further preferably 20 N or more. The upper limit of the pull-out strength is not limited, and may be 50 N, for example.
[0028] The pull-out strength is the maximum tensile stress measured when the fluororesin layer is pulled out from the conductor by a distance of 30 mm in the long-axis direction (length direction) at a speed of 50 mm / min.
[0029] It should be noted that, in an insulated wire having a substantially rectangular cross-sectional shape, a plane having a width sufficient to measure the peel strength is usually present on the conductor. On the other hand, in an insulated wire having a substantially circular cross-sectional shape, a plane having a width sufficient to measure the peel strength is usually not present on the conductor, and in this respect, the insulated wire having a substantially rectangular cross-sectional shape is different from the insulated wire having a substantially circular cross-sectional shape.
[0030] Next, the configuration of the conductor and the coating layer will be described in more detail. In the present disclosure, the first insulated wire and the second insulated wire may be simply referred to as "insulated wires".
[0031] (conductor)
[0032] The conductor may be a single wire, a group of wires, a twisted wire, etc., preferably a single wire. The cross-sectional shape of the conductor may be either approximately rectangular or approximately circular.
[0033] The conductor is not particularly limited as long as it is made of a conductive material, and can be made of materials such as copper, copper alloy, aluminum, aluminum alloy, iron, silver, nickel, etc., preferably copper, copper alloy, aluminum or aluminum alloy. In addition, conductors plated with silver plating, nickel plating, etc. can also be used. As copper, oxygen-free copper, low-oxygen copper, copper alloys, etc. can be used.
[0034] When the cross section of the conductor is approximately rectangular, that is, when the conductor is a flat conductor, the width of the cross section of the conductor can be 1 mm to 75 mm, and the thickness of the cross section of the conductor can be 0.1 mm to 30 mm. The outer diameter of the conductor can be 6.5 mm or more and 200 mm or less. In addition, the ratio of the width to the thickness can be greater than 1 and less than 30.
[0035] When the cross section of the conductor is substantially circular, that is, when the conductor is a round conductor, the diameter of the conductor is preferably 0.1 mm to 10 mm, more preferably 0.3 mm to 3 mm.
[0036] From the viewpoint of more firmly adhering the conductor to the fluororesin layer, the surface roughness Sz of the conductor is preferably 0.2 μm to 12 μm, more preferably 1 μm or more, further preferably 5 μm or more, and more preferably 10 μm or less.
[0037] The surface roughness of the conductor can be adjusted by treating the conductor using a surface treatment method such as etching, sandblasting, or laser treatment. In addition, the surface of the conductor can also be provided with concavities and convexities by surface treatment. The smaller the distance between the concavities and convexities, the better, for example, 5 μm or less. In addition, regarding the size of the concavities and convexities, for example, the area of each concave portion when the convex portion relative to the unprocessed surface is cut is 1 μm. 2 The concavoconvex shape may be a single concavoconvex shape of a crater, or may be branched into an ant's nest shape.
[0038] (Fluororesin layer)
[0039] The fluororesin layer contains a melt-processable fluororesin. In the present disclosure, melt-processability means that the polymer can be melted and processed using existing processing equipment such as an extruder and an injection molding machine. Therefore, the melt-processable fluororesin generally has a melt flow rate of 0.01 g / 10 minutes to 500 g / 10 minutes as measured by the measurement method described below.
[0040] The melt flow rate of the fluororesin is preferably 10 g / 10 minutes to 100 g / 10 minutes. The upper limit of the melt flow rate is more preferably 80 g / 10 minutes or less, and further preferably 70 g / 10 minutes or less. When the melt flow rate is 100 g / 10 minutes or less, it is preferred from the perspective of being able to suppress cracks when the wire coated with the resin is bent. The lower limit of the melt flow rate is preferably 20 g / 10 minutes or more, and more preferably 50 g / 10 minutes or more. When the melt flow rate is 10 g / 10 minutes or more, it is preferred from the perspective of being able to suppress the occurrence of melt fracture when the resin is coated and molded. By making the melt flow rate of the fluororesin within the above range, a fluororesin layer can be easily formed, and the resulting fluororesin layer has excellent mechanical strength and appearance.
[0041] In the present disclosure, the melt flow rate of the fluororesin is a value obtained as the mass (g / 10 minutes) of the polymer flowing out from a nozzle having an inner diameter of 2.1 mm and a length of 8 mm at 372°C and a load of 5 kg per 10 minutes using a melt flow indexer (manufactured by Yasuda Seiki Co., Ltd.) in accordance with ASTM D1238.
[0042] The melting point of the fluororesin is preferably 200°C to 322°C, more preferably 210°C or higher, further preferably 220°C or higher, particularly preferably 240°C or higher, and more preferably 320°C or lower.
[0043] The melting point can be determined using a differential scanning calorimeter [DSC].
[0044] Examples of melt-processable fluororesins include tetrafluoroethylene (TFE) / fluoroalkyl vinyl ether (FAVE) copolymers, tetrafluoroethylene (TFE) / hexafluoropropylene (HFP) copolymers, TFE / ethylene copolymers [ETFE], TFE / ethylene / HFP copolymers, ethylene / chlorotrifluoroethylene (CTFE) copolymers [ECTFE], polychlorotrifluoroethylene [PCTFE], CTFE / TFE copolymers, polyvinylidene fluoride [PVdF], TFE / vinylidene fluoride (VdF) copolymers [VT], polyvinyl fluoride [PVF], TFE / VdF / CTFE copolymers [VTC], and TFE / HFP / VdF copolymers.
[0045] The fluororesin is preferably at least one selected from the group consisting of TFE / FAVE copolymers and TFE / HFP copolymers, from the viewpoints of excellent heat resistance, moldability, and electrical properties, and stronger adhesion between the conductor and the fluororesin layer.
[0046] TFE / FAVE copolymer is a copolymer containing tetrafluoroethylene (TFE) units and fluoroalkyl vinyl ether (FAVE) units.
[0047] Examples of FAVE constituting the FAVE unit include those selected from the group consisting of the following general formula (1):
[0048] CF2=CFO(CF2CFY 1 O) p -(CF2CF2CF2O) q -Rf (1)
[0049] (In the formula, Y 1 represents F or CF3, Rf represents a perfluoroalkyl group having 1 to 5 carbon atoms, p represents an integer of 0 to 5, and q represents an integer of 0 to 5. ) and the general formula (2):
[0050] CFX=CXOCF2OR 1 (2)
[0051] (wherein, X is the same or different and represents H, F or CF3, R 1 It represents a linear or branched fluoroalkyl group having 1 to 6 carbon atoms which may contain 1 to 2 atoms of at least one kind selected from the group consisting of H, Cl, Br and I, or a cyclic fluoroalkyl group having 5 or 6 carbon atoms which may contain 1 to 2 atoms of at least one kind selected from the group consisting of H, Cl, Br and I. At least one of the group consisting of monomers represented by ).
[0052] As FAVE, the monomer represented by the general formula (1) is preferred, more preferably at least one selected from the group consisting of perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether) (PEVE) and perfluoro(propyl vinyl ether) (PPVE), further preferably at least one selected from the group consisting of PEVE and PPVE, and particularly preferably PPVE.
[0053] From the perspective of more firmly adhering the conductor to the fluororesin layer, the content of the FAVE unit in the TFE / FAVE copolymer is preferably 1.0 mol% to 30.0 mol% relative to all monomer units, more preferably 1.2 mol% or more, further preferably 1.4 mol% or more, further preferably 1.6 mol% or more, particularly preferably 1.8 mol% or more, more preferably 3.5 mol% or less, further preferably 3.2 mol% or less, further preferably 2.9 mol% or less, and particularly preferably 2.6 mol% or less.
[0054] From the perspective of more firmly adhering the conductor to the fluororesin layer, the content of the TFE unit in the TFE / FAVE copolymer is preferably 99.0 mol% to 70.0 mol% relative to all monomer units, more preferably 96.5 mol% or more, further preferably 96.8 mol% or more, further preferably 97.1 mol% or more, particularly preferably 97.4 mol% or more, more preferably 98.8 mol% or less, further preferably 98.6 mol% or less, further preferably 98.4 mol% or less, and particularly preferably 98.2 mol% or less.
[0055] In the present disclosure, the content of each monomer unit in the copolymer is expressed by 19 Determined by F-NMR method.
[0056] The TFE / FAVE copolymer may also contain monomer units from monomers copolymerizable with TFE and FAVE. In this case, the content of the monomers copolymerizable with TFE and FAVE is preferably 0 to 29.0 mol%, more preferably 0.1 mol% to 5.0 mol%, and further preferably 0.1 mol% to 1.0 mol%, relative to all monomer units of the TFE / FAVE copolymer.
[0057] Examples of monomers copolymerizable with TFE and FAVE include HFP, CZ 1 Z 2 =CZ 3 (CF2) n Z 4 (Where Z 1 , Z 2 and Z 3 Same or different, means H or F, Z 4 represents H, F or Cl, n represents an integer of 2 to 10) and CF2=CF-OCH2-Rf 1 (Where Rf 1 An alkyl perfluorovinyl ether derivative represented by (represents a perfluoroalkyl group having 1 to 5 carbon atoms), a monomer having a functional group, etc. Among them, HFP is preferred.
[0058] The TFE / FAVE copolymer is preferably at least one selected from the group consisting of a copolymer consisting only of a TFE unit and a FAVE unit and the above-mentioned TFE / HFP / FAVE copolymer, and more preferably a copolymer consisting only of a TFE unit and a FAVE unit.
[0059] From the viewpoint of heat resistance and stress crack resistance, the melting point of the TFE / FAVE copolymer is preferably 240° C. to 322° C., more preferably 285° C. or higher, more preferably 320° C. or lower, further preferably 315° C. or lower, particularly preferably 310° C. or lower. The melting point can be measured using a differential scanning calorimeter [DSC].
[0060] The glass transition temperature (Tg) of the TFE / FAVE copolymer is preferably 70° C. to 110° C., more preferably 80° C. or higher, and more preferably 100° C. or lower. The glass transition temperature can be measured by dynamic viscoelasticity measurement.
[0061] From the aspect of electrical properties, the relative dielectric constant of the TFE / FAVE copolymer is preferably 2.4 or less, more preferably 2.1 or less, and the lower limit is not particularly limited, but preferably 1.8 or more. The relative dielectric constant is a value obtained by measuring the changes in the resonant frequency and the electric field strength at a temperature of 20°C to 25°C using a network analyzer HP8510C (manufactured by Hewlett-Packard) and a cavity resonator.
[0062] TFE / HFP copolymer is a copolymer containing tetrafluoroethylene (TFE) units and hexafluoropropylene (HFP) units.
[0063] From the viewpoint of more firmly adhering the conductor to the fluororesin layer, the content of the HFP unit in the TFE / HFP copolymer is preferably 0.1 mol% to 30.0 mol% based on all monomer units, more preferably 0.7 mol% or more, further preferably 1.4 mol% or more, and more preferably 10.0 mol% or less.
[0064] From the viewpoint of more firmly adhering the conductor to the fluororesin layer, the content of the TFE unit in the TFE / HFP copolymer is preferably 70.0 mol% to 99.9 mol% based on all monomer units, more preferably 90.0 mol% or more, more preferably 99.3 mol% or less, and further preferably 98.6 mol%.
[0065] The TFE / HFP copolymer may also contain monomer units derived from monomers copolymerizable with TFE and HFP. In this case, the content of the monomers copolymerizable with TFE and HFP is preferably 0 to 29.9 mol%, more preferably 0.1 mol% to 5.0 mol%, and even more preferably 0.1 mol% to 1.0 mol%, relative to all monomer units of the TFE / HFP copolymer.
[0066] Examples of monomers copolymerizable with TFE and HFP include FAVE, CZ 1 Z 2 =CZ 3 (CF2) n Z 4 (Where Z 1 , Z 2 and Z 3 Same or different, means H or F, Z 4 represents H, F or Cl, n represents an integer of 2 to 10) and CF2=CF-OCH2-Rf 1 (Where Rf 1 represents a perfluoroalkyl group having 1 to 5 carbon atoms), an alkyl perfluorovinyl ether derivative represented by (represents a perfluoroalkyl group having 1 to 5 carbon atoms), a monomer having a functional group, etc. Among them, FAVE is preferred.
[0067] The melting point of the TFE / HFP copolymer is preferably 200°C to 322°C, more preferably 210°C or higher, further preferably 220°C or higher, particularly preferably 240°C or higher, more preferably 320°C or lower, further preferably less than 300°C, particularly preferably 280°C or lower.
[0068] The glass transition temperature (Tg) of the TFE / HFP copolymer is preferably 60°C to 110°C, more preferably 65°C or higher, and more preferably 100°C or lower.
[0069] The fluororesin preferably has a functional group. When the fluororesin has a functional group, the conductor and the fluororesin layer can be more firmly adhered to each other.
[0070] The functional group is preferably at least one selected from the group consisting of a carbonyl-containing group, an amino group, a hydroxyl group, a -CF2H group, an olefin group, an epoxy group, and an isocyanate group.
[0071] The carbonyl-containing group is a group containing a carbonyl group (-C(=O)-) in its structure. Examples of the carbonyl-containing group include:
[0072] Carbonate group [-OC(=O)-OR 3 (Where R 3 is an alkyl group having 1 to 20 carbon atoms or an alkyl group having 2 to 20 carbon atoms containing an ethereal oxygen atom)],
[0073] Acyl [-C(=O)-R 3 (Where R 3 is an alkyl group having 1 to 20 carbon atoms or an alkyl group having 2 to 20 carbon atoms containing an ethereal oxygen atom)],
[0074] Haloformyl [-C(=O)X 5 , X 5 is a halogen atom],
[0075] Formyl [-C(=O)H],
[0076] Formula: -R 4 -C(=O)-R 5 (Where R 4 is a divalent organic group having 1 to 20 carbon atoms, R 5 is a monovalent organic group having 1 to 20 carbon atoms),
[0077] Formula: -OC(=O)-R 6 (Where R 6 is an alkyl group having 1 to 20 carbon atoms or an alkyl group having 2 to 20 carbon atoms containing an ethereal oxygen atom,
[0078] Carboxyl [-C(=O)OH],
[0079] Alkoxycarbonyl [-C(=O)OR 7 (Where R 7 is a monovalent organic group having 1 to 20 carbon atoms)],
[0080] Carbamoyl [-C(=O)NR 8 R 9 (Where R 8 and R 9may be the same or different and are a hydrogen atom or a monovalent organic group having 1 to 20 carbon atoms)],
[0081] Anhydride bond [—C(═O)—OC(═O)—] and the like.
[0082] As R 3 Specific examples of R include methyl, ethyl, propyl, isopropyl, and butyl. 4 Specific examples of R include methylene, -CF2-, -C6H4-, etc. 5 Specific examples of R include methyl, ethyl, propyl, isopropyl, and butyl. 7 Specific examples of R include methyl, ethyl, propyl, isopropyl, butyl, etc. 8 and R 9 Specific examples of include a hydrogen atom, a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, and a phenyl group.
[0083] The hydroxyl group is a group represented by -OH or a group including a group represented by -OH. In the present disclosure, -OH constituting a carboxyl group is not included in the hydroxyl group. Examples of the hydroxyl group include -OH, hydroxymethyl, and hydroxyethyl.
[0084] An olefin group is a group having a carbon-carbon double bond. Examples of the olefin group include the following formulas:
[0085] -CR 10 =CR 11 R 12
[0086] (Where R 10 , R 11 and R 12 The functional group may be the same or different and is represented by a hydrogen atom, a fluorine atom or a monovalent organic group having 1 to 20 carbon atoms, and is preferably at least one selected from the group consisting of -CF=CF2, -CH=CF2, -CF=CHF, -CF=CH2 and -CH=CH2.
[0087] The isocyanate group is a group represented by -N=C=O.
[0088] In addition, examples of the functional group include non-fluorinated alkyl groups or partially fluorinated alkyl groups such as a -CH3 group and a -CFH2 group.
[0089] From the viewpoint of more firmly adhering the conductor to the fluororesin layer, the number of functional groups of the fluororesin is 6 The number of carbon atoms is preferably 5 to 2000. 6The number of functional groups is more preferably 50 or more, further preferably 100 or more, particularly preferably 200 or more, more preferably 1500 or less, further preferably 1300 or less, particularly preferably 1100 or less, and most preferably 1000 or less.
[0090] In addition, since a coating layer with excellent electrical properties can be formed, the number of functional groups of the fluororesin per 10 6 The number of carbon atoms may be less than 5.
[0091] The functional groups are functional groups present at the main chain end or side chain end of the copolymer (fluororesin), and functional groups present in the main chain or side chain, preferably present at the main chain end. Examples of the functional groups include -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2, -OH, -CH2OH, etc., preferably at least one selected from the group consisting of -CF2H, -COF, -COOH, -COOCH3 and -CH2OH. -COOH includes a dicarboxylic anhydride group (-CO-O-CO-) formed by two -COOH bonds.
[0092] The identification of the types of the functional groups and the measurement of the number of the functional groups can be performed using infrared spectroscopy.
[0093] The number of functional groups is specifically determined by the following method. First, the copolymer is melted at 330°C to 340°C for 30 minutes and compression molded to produce a film with a thickness of 0.20 mm to 0.25 mm. The film is analyzed by Fourier transform infrared spectroscopy to obtain an infrared absorption spectrum of the copolymer, and a differential spectrum is obtained from the background spectrum in which the functional groups are completely fluorinated and do not exist. According to the following formula (A), the number of functional groups per 1×10 6 The number of functional groups N per carbon atom.
[0094] N=I×K / t(A)
[0095] I: Absorbance
[0096] K: Correction coefficient
[0097] t: film thickness (mm)
[0098] For reference, regarding the functional groups in the present disclosure, the absorption frequency, molar absorption coefficient, and correction coefficient are shown in Table 1. The molar absorption coefficient was determined from FT-IR measurement data of a low-molecular model compound.
[0099] [Table 1]
[0100] Table 1
[0101]
[0102] It should be noted that the absorption frequencies of -CH2CF2H, -CH2COF, -CH2COOH, -CH2COOCH3, and -CH2CONH2 are several tens of kaise (cm-1) lower than the absorption frequencies of -CF2H, -COF, free -COOH, and bonded -COOH, -COOCH3, and -CONH2 shown in the table, respectively. 1 ).
[0103] Thus, for example, the functional group number of -COF refers to the absorption frequency 1883 cm-1 due to -CF2COF. 1 The number of functional groups obtained from the absorption peak at 1840 cm-1 due to -CH2COF 1 The total number of functional groups found from the absorption peak at .
[0104] The above-mentioned number of functional groups can be the total number of -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2 and -CH2OH, or the total number of -CF2H, -COF, -COOH, -COOCH3 and -CH2OH.
[0105] The functional groups are introduced into the fluororesin (copolymer) by, for example, a chain transfer agent or a polymerization initiator used when manufacturing the fluororesin. For example, when an alcohol is used as a chain transfer agent or a peroxide having a -CH2OH structure is used as a polymerization initiator, -CH2OH is introduced into the main chain end of the fluororesin. In addition, by polymerizing a monomer having a functional group, the functional group is introduced into the side chain end of the fluororesin. The fluororesin may contain units derived from a monomer having a functional group.
[0106] Examples of monomers having a functional group include cyclic hydrocarbon monomers having a dicarboxylic anhydride group (-CO-O-CO-) and a polymerizable unsaturated group in the ring as described in Japanese Patent Application Laid-Open No. 2006-152234, and monomers having a functional group (f) as described in International Publication No. 2017 / 122743. Examples of monomers having a functional group include monomers having a carboxyl group (maleic acid, itaconic acid, citraconic acid, undecylenic acid, etc.); monomers having an anhydride group (itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, maleic anhydride, etc.), and monomers having a hydroxyl group or an epoxy group (hydroxybutyl vinyl ether, glycidyl vinyl ether, etc.).
[0107] The fluororesin can be produced, for example, by appropriately mixing monomers that will serve as structural units thereof and additives such as a polymerization initiator and subjecting them to conventionally known methods such as emulsion polymerization and suspension polymerization.
[0108] The fluororesin layer may contain other ingredients as required. As other ingredients, crosslinking agents, antistatic agents, heat stabilizers, foaming agents, foaming nucleating agents, antioxidants, surfactants, photopolymerization initiators, anti-wear agents, surface modifiers, various pigments of organic / inorganic systems, copper poison inhibitors, bubble preventers, close fit imparting agents, lubricants, processing aids, colorants, phosphorus stabilizers, lubricants, mold release agents, sliding materials, ultraviolet absorbers, dye pigments, reinforcing materials, anti-drip agents, filling materials, curing agents, ultraviolet curing agents, flame retardants and other additives may be cited. As the content of other ingredients in the fluororesin layer, relative to the mass of the fluororesin in the fluororesin layer, preferably less than 30 mass%, more preferably less than 10 mass%, further preferably less than 5 mass%, the lower limit is not particularly limited, and can be more than 0 mass%. That is, the fluororesin layer may not contain other ingredients.
[0109] The fluororesin layer may contain additives and fillers for the purpose of improving mechanical properties and molding processability. Examples thereof include glass fibers, carbon fibers, carbon milled fibers, carbon nanotubes, carbon nanohorns, metal fibers, asbestos, rock wool, and the like. fibrous fillers such as fullerene, talc, wollastonite, zeolite, mica, clay, pyrophyllite, graphite, silica, bentonite, asbestos, aluminum silicate and other silicates, silicon oxide, magnesium oxide, calcium oxide, aluminum oxide, zirconium oxide, titanium oxide, iron oxide and other metal compounds, carbonates such as calcium carbonate, magnesium carbonate, dolomite, sulfates such as calcium sulfate and barium sulfate, hydroxides such as calcium hydroxide and aluminum hydroxide, glass beads, glass flakes, glass powder, boron nitride, silicon carbide, carbon black, graphite, etc.
[0110] In order to improve the low dielectric constant, it is also effective to make the fluororesin layer have bubbles. As inorganic foaming nucleating agents, boron nitride, talc, zeolite, mica, aluminum silicate, calcium silicate, calcium carbonate, dolomite, magnesium oxide, magnesium hydroxide, aluminum oxide, aluminum hydroxide, antimony trioxide, titanium oxide, iron oxide, etc. can be exemplified. During wire processing, bubbles can be obtained by injecting inactive gases, nitrogen, carbon dioxide, argon, helium, etc. into the coating material and foaming it. Bubbles can be obtained by mixing fine hollow particles, hollow capsules, hollow balls, hollow polymer particles, etc. into the material. For example, acrylic hollow particles, silica hollow particles, aluminum oxide hollow particles, ceramic hollow particles, glass balls, glass hollow particles, etc. can be cited. The size of the hollow particles is preferably less than 10 μm, more preferably less than 1 μm, and further preferably less than 500nm. The lower limit is not particularly limited and can be more than 30nm.
[0111] From the viewpoint of insulation properties, the thickness of the fluororesin layer is preferably 40 μm to 300 μm, more preferably 50 μm or more, further preferably 60 μm or more, and more preferably 250 μm or less, further preferably 200 μm or less.
[0112] The relative dielectric constant of the fluororesin layer is preferably 2.5 or less, more preferably 2.4 or less, further preferably 2.3 or less, further preferably 2.2 or less, particularly preferably 2.1 or less, and preferably 1.8 or more. The relative dielectric constant is a value obtained by measuring changes in resonance frequency and electric field intensity at a temperature of 20°C to 25°C using a network analyzer HP8510C (manufactured by Hewlett-Packard) and a cavity resonator.
[0113] From the viewpoint of insulation properties, the partial discharge inception voltage of the insulated wire measured at 25° C. preferably satisfies the following relationship.
[0114] Partial discharge inception voltage (V) ≥ 5.5 × t + 600
[0115] t: Film thickness of fluororesin layer (μm)
[0116] The partial discharge inception voltage of the insulated wire is preferably not easily changed even when the temperature changes. The change rate calculated by the following formula from the partial discharge inception voltage measured at 25°C and the partial discharge inception voltage measured at 200°C of the insulated wire is preferably less than 10%, more preferably less than 5%.
[0117] Change rate (%) = [(partial discharge inception voltage measured at 25°C) - (partial discharge inception voltage measured at 200°C)] / (partial discharge inception voltage measured at 25°C) × 100
[0118] (Other layers)
[0119] The insulated wire of the present disclosure may further include another layer formed on the outer periphery of the fluororesin layer.
[0120] In the insulated wire of the present disclosure, the conductor and the fluororesin layer are in close contact with each other with sufficient strength, and therefore, no other layer exists between the conductor and the fluororesin layer, and the conductor and the fluororesin layer are in direct close contact with each other.
[0121] As other layers, a layer formed on the periphery of the fluororesin layer and containing a thermoplastic resin can be cited. As thermoplastic resins, fluororesins, thermoplastic polyimide resins, thermoplastic polyamide-imide resins, polyamide resins, polyolefin resins, modified polyolefin resins, polyethylene resins, polyesters, ethylene / vinyl alcohol copolymers, polyacetal resins, polyurethane resins, polyphenylene ether resins, polycarbonate resins, acrylic resins, styrene resins, acrylonitrile / butadiene / styrene resins (ABS), vinyl chloride resins, cellulose resins, polysulfone resins, polyethersulfone resins (PES), polyetherimide resins, polyphenylene sulfide, polyethylene terephthalate, etc. can be cited.
[0122] (Manufacturing method of insulated electric wire)
[0123] The insulated wire of the present disclosure can be produced, for example, by heating and melting a fluororesin using an extruder, and extruding the molten fluororesin onto a conductor to form a coating layer.
[0124] In this case, by extruding the molten fluororesin onto the conductor heated to a temperature higher than the temperature of the molten fluororesin, an insulated wire in which the conductor and the fluororesin layer are closely adhered to each other with sufficient strength can be obtained.
[0125] The extrusion molding machine is not particularly limited, and an extrusion molding machine including a barrel, a die head, and a pipe joint having a through port for feeding out a conductor can be used.
[0126] The temperature of the molten fluororesin is usually above the melting point of the fluororesin, preferably a temperature 15°C higher than the melting point of the fluororesin, more preferably a temperature 20°C higher than the melting point of the fluororesin, further preferably a temperature 25°C higher than the melting point of the fluororesin, further preferably a temperature 40°C higher than the melting point of the fluororesin, particularly preferably a temperature 80°C higher than the melting point of the fluororesin, and most preferably a temperature 100°C higher than the melting point of the fluororesin. The upper limit of the temperature of the molten fluororesin is not limited, but is preferably 510°C or less, more preferably 450°C or less, from the perspective of suppressing thermal decomposition of the resin during wire molding and suppressing discoloration of the resin during wire molding. The temperature of the molten fluororesin can be adjusted by adjusting the temperature of the barrel of the extruder, the temperature of the die, etc. The temperature of the molten fluororesin can be determined, for example, by measuring the temperature of the fluororesin discharged from the die outlet using a thermocouple.
[0127] The temperature of the conductor after heating is higher than the temperature of the fluororesin in a molten state, preferably 15° C. or higher, more preferably 20° C. or higher, and further preferably 30° C. or higher. The upper limit of the temperature of the conductor after heating is not limited, and is, for example, 700° C. or lower.
[0128] The temperature of the heated conductor can be determined by measuring the temperature of the conductor between the heating device and the extruder using, for example, a contact thermometer or a non-contact thermometer.
[0129] The temperature of the heated conductor can be adjusted by heating the conductor before feeding it into the extruder using a heating device. As a heating device, any device that heats a certain range at once at high temperature, such as a halogen heater, a carbon heater, a tungsten heater, a hot air heating device, an induction heating device, a microwave heating device, a superheated steam generating device, a burner, etc., can be used. The size, shape, number of devices, and number of heating sources are not limited. In addition, different methods can be used in combination with each other, and multiple heat sources can be used. For the reason that a large range can be irradiated uniformly at once, it is preferred to use a halogen heater for heating.
[0130] The heating conditions are not particularly limited as long as the conductor temperature when the conductor contacts the resin is higher than the molding temperature (head temperature), and the distance between the molding machine and the heating device can be close or far. In addition, different heating devices, heating pipes, insulation pipes, and insulation materials can be provided around the running line after passing through the conductor heating range for the purpose of heat preservation of the conductor.
[0131] The line speed during extrusion molding may be 0.1 m / min to 50 m / min, and is preferably 20 m / min or less.
[0132] After the fluororesin layer is formed, the insulated wire may be cooled. The cooling method is not particularly limited, and may be water cooling, air cooling, or the like. When the insulated wire is cooled by air cooling, it can be cooled at a moderate speed, so there is a tendency for the thickness of the fluororesin layer to become uniform.
[0133] After forming the fluororesin layer, the insulated wire may be subjected to heat treatment. The heat treatment may be performed after forming the fluororesin layer, and may be performed before cooling or after cooling. The temperature of the heat treatment is usually higher than the glass transition temperature of the fluororesin, preferably higher than a temperature 15°C higher than the melting point, and preferably lower than a temperature 50°C higher than the melting point of the fluororesin.
[0134] After forming the fluororesin layer, the material for forming other layers may be extruded on the fluororesin layer to form the other layers. Alternatively, the fluororesin layer may be formed by simultaneous multi-layer melt extrusion molding and the other layers may be formed on the fluororesin layer.
[0135] The insulated wire disclosed in the present invention can be suitably used for, for example, LAN cables, USB cables, Lightning cables, HDMI (registered trademark) cables, QSFP cables, aerospace wires, underground power transmission cables, submarine power cables, high-voltage cables, superconducting cables, packaged wires, automotive wires, wiring harnesses and electrical equipment, robot and FA wires, OA equipment wires, information equipment wires (optical fiber cables, LAN cables, HDMI cables, Lightning cables, audio cables, etc.), internal wiring for communication base stations, high-current internal wiring (inverters, power conditioners, battery systems, etc.), internal wiring for electronic equipment, small electronic equipment and mobile wiring, movable part wiring, internal wiring for electrical equipment, internal wiring for measuring equipment, power cables (for construction, wind power / solar power generation, etc.), cables for control and measurement wiring, cables for motors, etc.
[0136] The insulated wire of the present invention can be wound and used as a coil. The insulated wire and coil of the present invention can be suitably used in electric devices or electronic devices such as motors, generators, and inductors. In addition, the insulated wire and coil of the present invention can be suitably used in electric devices or electronic devices such as vehicle-mounted motors, vehicle-mounted generators, and vehicle-mounted inductors.
[0137] Although the embodiments have been described above, it should be understood that various changes in the embodiments and details may be made without departing from the spirit and scope of the claims.
[0138] <1> According to a first aspect of the present disclosure, there is provided an insulated wire comprising a conductor and a fluororesin layer formed on the conductor and containing a melt-processable fluororesin, wherein a peel strength measured by peeling the fluororesin layer from the conductor is 0.30 N / mm or more.
[0139] <2> According to a second aspect of the present disclosure, there is provided the insulated wire according to the first aspect, wherein the conductor has a substantially rectangular cross-sectional shape.
[0140] <3> According to a third aspect of the present disclosure, there is provided an insulated wire comprising a conductor and a fluororesin layer formed on the conductor and containing a melt-processable fluororesin, wherein a pull-out strength measured by pulling out the fluororesin from the conductor is 4N or more.
[0141] <4> According to a fourth aspect of the present disclosure, there is provided the insulated wire according to the third aspect, wherein a cross-sectional shape of the conductor is substantially circular.
[0142] <5> According to a fifth aspect of the present disclosure, there is provided an insulated wire according to any one of the first to fourth aspects, wherein the fluororesin layer is formed by extruding the molten fluororesin onto the conductor heated to a temperature higher than the temperature of the molten fluororesin.
[0143] <6> According to a sixth aspect of the present disclosure, there is provided the insulated wire according to any one of the first to fifth aspects, wherein the conductor is made of at least one selected from the group consisting of copper, copper alloys, aluminum, and aluminum alloys.
[0144] <7> According to a seventh aspect of the present disclosure, there is provided the insulated wire according to any one of the first to sixth aspects, wherein the conductor has a surface roughness Sz of 0.2 μm to 12 μm.
[0145] <8> According to an eighth aspect of the present disclosure, there is provided the insulated wire according to any one of the first to seventh aspects, wherein the fluororesin layer has a thickness of 40 μm to 300 μm.
[0146] <9> According to a ninth aspect of the present disclosure, there is provided the insulated wire according to any one of the first to eighth aspects, wherein the fluororesin layer has a relative dielectric constant of 2.5 or less.
[0147] <10> According to a tenth aspect of the present disclosure, there is provided an insulated wire according to any one of the first to ninth aspects, wherein a partial discharge inception voltage measured at 25° C. satisfies the following relational expression.
[0148] Partial discharge inception voltage (V) ≥ 5.5 × t + 600
[0149] t: Film thickness of fluororesin layer (μm)
[0150] <11> According to an eleventh aspect of the present disclosure, there is provided the insulated wire according to any one of the first to tenth aspects, wherein the rate of change calculated by the following formula is less than 10%.
[0151] Change rate (%) = [(partial discharge inception voltage measured at 25°C) - (partial discharge inception voltage measured at 200°C)] / (partial discharge inception voltage measured at 25°C) × 100
[0152] <12> According to a twelfth aspect of the present disclosure, there is provided the insulated wire according to any one of the first to eleventh aspects, wherein the fluororesin has a melt flow rate of 0.1 g / 10 min to 120 g / 10 min.
[0153] <13> According to a 13th aspect of the present disclosure, there is provided the insulated wire according to any one of the 1st to 12th aspects, wherein the fluororesin has a melting point of 240°C to 320°C.
[0154] <14> According to a 14th aspect of the present disclosure, there is provided an insulated wire according to any one of the 1st to 13th aspects, wherein the fluororesin has a functional group, and the number of the functional groups of the fluororesin is 10 6 The number of carbon atoms ranges from 5 to 2000.
[0155] <15> According to a fifteenth aspect of the present disclosure, there is provided the insulated wire according to any one of the first to fourteenth aspects, wherein the fluororesin contains a tetrafluoroethylene unit and a fluoroalkyl vinyl ether unit.
[0156] <16> According to a sixteenth aspect of the present disclosure, there is provided the insulated wire according to the fifteenth aspect, wherein the content of the fluoroalkyl vinyl ether unit in the fluororesin is 1.0 mol % to 30.0 mol % based on all monomer units.
[0157] <17> According to a seventeenth aspect of the present disclosure, there is provided the insulated wire according to any one of the first to fourteenth aspects, wherein the fluororesin contains a tetrafluoroethylene unit and a hexafluoropropylene unit.
[0158] <18> According to an eighteenth aspect of the present disclosure, there is provided an insulated wire based on any one of the first to seventeenth aspects, wherein the fluororesin has at least one functional group selected from the group consisting of a carbonyl-containing group, an amino group, a hydroxyl group, a -CF2H group, an olefin group, an epoxy group, and an isocyanate group.
[0159] <19> According to a 19th aspect of the present disclosure, there is provided a method for producing an insulated wire using an extrusion molding machine to produce the insulated wire according to the 1st aspect to the 18th aspect, wherein:
[0160] The fluororesin is heated to melt the fluororesin, and the molten fluororesin is extruded onto a conductor heated to a temperature higher than the temperature of the molten fluororesin, thereby forming the fluororesin layer on the conductor.
[0161] <20> According to a 20th aspect of the present disclosure, there is provided the production method according to the 19th aspect, wherein the conductor is heated using a halogen heater.
[0162] Example
[0163] Next, embodiments of the present disclosure will be described with reference to examples, but the present disclosure is not limited to the above examples.
[0164] Each numerical value in the examples was measured by the following method.
[0165] (Melt Flow Rate (MFR))
[0166] According to ASTM D1238, the mass (g / 10 minutes) of the copolymer flowing out from a nozzle having an inner diameter of 2.1 mm and a length of 8 mm at 372°C and a load of 5 kg per 10 minutes was determined using a melt flow indexer (manufactured by Yasuda Seiki Co., Ltd.).
[0167] (Melting Point)
[0168] The temperature was determined as the temperature corresponding to the maximum value of the heat of fusion in the heat of fusion curve when the temperature was increased at a rate of 10°C / min using a differential scanning calorimeter [DSC].
[0169] (Composition of fluororesin)
[0170] pass 19 The measurement was carried out by F-NMR method.
[0171] (Number of functional groups)
[0172] The fluororesin was melted at 330°C to 340°C for 30 minutes and compression molded to produce a film with a thickness of 0.20 mm to 0.25 mm. The film was scanned 40 times by a Fourier transform infrared spectrometer [FT-IR (trade name: 1760X, manufactured by PerkinElmer) and analyzed to obtain an infrared absorption spectrum, which was a differential spectrum from the background spectrum in which the functional groups were completely fluorinated and did not exist. According to the following formula (A), the absorption peak of the specific functional group appearing in the differential spectrum was used to calculate the relative amount of 10% of the fluororesin. 6 The number of functional groups N per carbon atom.
[0173] N=I×K / t(A)
[0174] I: Absorbance
[0175] K: Correction coefficient
[0176] t: film thickness (mm)
[0177] For reference, regarding the functional groups in the present disclosure, the absorption frequency, molar absorption coefficient, and correction coefficient are shown in Table 2. The molar absorption coefficient was determined from FT-IR measurement data of a low-molecular model compound.
[0178] [Table 2]
[0179] Table 2
[0180]
[0181] (Thickness of fluororesin layer)
[0182] The measurement is carried out by means of a micrometer.
[0183] (Conductor temperature when the conductor contacts the resin)
[0184] A non-contact radiation temperature sensor (manufactured by Japan Sensor Co., Ltd.) was fixed in such a manner that the focal point was located at a position 10 cm away from the end of the downstream side of the moving direction of the running line of the conductor heating range to the moving direction of the running line, and the conductor temperature outside the conductor heating range was measured. When the cross-sectional shape of the conductor is approximately rectangular, the measurement surface is respectively measured on the long face (main face) and the short face (side face) of the conductor, and as a correction, it is set to measure the temperature of the conductor surface (room temperature) of each face before heating using a contact thermometer (manufactured by Anritsu Meter Co., Ltd.). The measurement angle is made perpendicular to the face, and a light shielding plate is set between the heat source and the temperature measurement part in order to avoid being affected by the heat source and the light reflection in the room.
[0185] Alternatively, a scanning contact thermometer may be fixed at a position 10 cm away from the end of the downstream side of the moving direction of the running line of the conductor heating range in the moving direction of the running line to measure the conductor surface temperature. Regarding the measuring surface, when the cross-sectional shape of the conductor is approximately rectangular, the long face (main face) and the short face (side face) of the conductor are measured respectively, and the conductor is arranged so that the conductor is in contact with the sensor vertically. In addition, when the cross-sectional shape of the conductor is circular, the running conductor is arranged so that the conductor is in contact with the sensor vertically.
[0186] In addition, when the cross-sectional shape of the conductor is approximately rectangular, it was confirmed that the temperature difference between the long surface (main surface) and the short surface (side surface) was within ±20°C.
[0187] (Conductor heating method)
[0188] The heating source was a halogen heater (lamp heater) with linear light (manufactured by Inflidge Industrial Co., Ltd.), and the length between the inlet of the extruder and the center lamp of the halogen heater was 35 cm. The heater was fixed so that the lamp was in vertical contact with the conductor surface.
[0189] (Resin temperature when conductor contacts resin)
[0190] Before starting the wire coating molding, a molten fluororesin was extruded from a die of an extruder, and the temperature of the extruded fluororesin at the die outlet was measured using a thermocouple.
[0191] (Surface roughness Sz)
[0192] 8000 μm was measured using a laser microscope (manufactured by KEYENCE)2 Surface roughness Sz in the field of view.
[0193] (Relative dielectric constant)
[0194] The wire bundle made using the above-mentioned melt flow index tester was cut into strips with a width of 2 mm and a length of 100 mm. The changes in the resonant frequency and electric field strength at 2.45 GHz were measured at a temperature of 20°C to 25°C using a network analyzer HP8510C (manufactured by Hewlett-Packard) and a cavity resonator.
[0195] (Extraction strength)
[0196] The measurement was performed using an AGS-X Autograph (5kN) (manufactured by Shimadzu Corporation). The wire was cut into 70 mm pieces, and after pre-peeling off only 20 mm of the coating from the end, a fixture with a hole thicker than the conductor diameter and thinner than the wire diameter was installed on the upper chuck. Next, only the stripped portion of the conductor was passed through the fixture, and the stripped conductor was fixed on the lower chuck. Then, the device was moved in the tensile direction, thereby extracting only the coating portion. The maximum point stress when stretched at 50 mm / min to a moving distance of 30 mm was taken as the extraction strength.
[0197] (Peel Strength)
[0198] Use AGS-J Autograph (50N) (manufactured by Shimadzu Corporation) for measurement. Cut two strips of 50 mm approximately parallel in the long axis direction, cut the film at both ends into a right angle along the short axis direction, peel off 10 mm at the end, and clamp it on the upper chuck. The conductor is fixed to the lower part in a horizontal manner in the long face direction. When moving the device in the tensile direction, use a clamp that moves in a linked manner in the transverse direction according to its longitudinal movement distance, and adjust the angle so that the peeled film is always perpendicular to the conductor in the long face direction. Measure the tensile stress when it is stretched at 100 mm / min to peel off 30 mm, and take its maximum point stress as the peel strength.
[0199] That is, using AGS-J Autograph (50N) (made by Shimadzu Corporation), the peel strength of the film on the main surface of the conductor (flat wire) of the insulated wire is measured. Here, the surface with the larger dimension in the width direction of the conductor in the two groups of opposing surfaces of the flat wire (the surface of the long side at right angles to the length direction of the conductor) is set as the main surface, and the surface conductor orthogonal to the main surface (the surface of the short side at right angles to the length direction) is set as the side. The dimension in the width direction of the conductor of the main surface is larger than the dimension in the width direction of the conductor of the side. Two roughly parallel incisions are formed along the length direction of the insulated wire on the film on one main surface, and then two incisions orthogonal to the length direction are formed at intervals of 50 mm. The end of the film formed with the incision is stripped from the conductor, and a clamping margin of 10 mm is set. With the other main surface facing down, the insulated wire is fixed to the fixture, the clamping margin is clamped to the upper chuck, and folded back 90 degrees. A fixture that moves in a manner that the angle between the insulated wire fixed to the fixture and the film is kept at 90 degrees is used. The film was peeled off by 30 mm at a tensile speed of 100 mm / min, and the tensile stress was measured. The stress at the maximum point was taken as the peel strength.
[0200] (Bending test)
[0201] When a U-shaped coil is used and both sides at 10 mm from the base point are bent R2 along the major axis direction (length direction), the case where at least one of floating, wrinkles and cracks occurs in the fluororesin layer is marked as ×, and the case where no floating, wrinkles and cracks occur is marked as 0.
[0202] (Appearance of insulated wire)
[0203] The case where the insulating coating produced at least one of melt fracture and discoloration was marked as ×, and the case where neither melt fracture nor discoloration occurred was marked as 0.
[0204] (Partial Discharge Inception Voltage (PDIV) (25℃, 200℃))
[0205] Two insulated wires were cut into 90 cm lengths, twisted while applying a tension of 13.5 N, and a twisted coil having 8 twists in a range of 125 mm in the center was produced. Then, the insulating film of 10 mm at the end of the sample was removed, and a partial discharge measuring device (DAC-PD-7 manufactured by Soken Electric Co., Ltd.) was used to apply a 50 Hz sinusoidal AC voltage between the conductors of the two insulated wires at an ambient temperature of 25°C (relative humidity 50%) or 200°C (relative humidity 50%), thereby measuring. The voltage rise rate was set to 50 V / sec, the voltage drop rate was set to 50 V / sec, the voltage holding time was set to 0 sec, and the voltage at the moment when a discharge of 10 pC or more was generated was taken as the partial discharge starting voltage.
[0206] In Examples and Comparative Examples, the following conductors were used.
[0207] Conductor 1: Copper flat wire with a rectangular cross section, thickness (short side) 2.0 mm, width (long side) 3.4 mm
[0208] Conductor 2: Copper round wire with a nearly circular cross section and a diameter of 1.0 mm
[0209] Comparative Example 1, Comparative Example 1'
[0210] The insulating film forming resin of Comparative Example 1 and Comparative Example 1' was a copolymer of tetrafluoroethylene and perfluoro(propyl vinyl ether) (PFA), with an MFR of 14 g / 10 minutes and a melting point of 306°C. In addition, the resin temperature at the die outlet during wire molding was set to 365°C, and a 200 μm extruded coating layer was formed. Here, the conductor temperature when the conductor came into contact with the resin was 260°C.
[0211] As an indicator of adhesion, the pull-out strength of the round wire in Comparative Example 1 was 2.0 N, and the peel strength of the flat wire in Comparative Example 1' was 0.001 N / mm. When the flat wire was bent, the film was also observed to have floating and wrinkles, so it was confirmed that the resin adhered to the conductor to the extent of hugging it, and was not adhered.
[0212] Comparative Example 2
[0213] The insulating film forming resin of Comparative Example 2 was a copolymer of tetrafluoroethylene and perfluoro(propyl vinyl ether) (PFA), with an MFR of 68 g / 10 minutes and a melting point of 295°C. In addition, the resin temperature at the die outlet during wire molding was set to 360°C, and a 200 μm extruded coating layer was formed. Here, the conductor temperature when the conductor came into contact with the resin was 300°C.
[0214] The peel strength of the flat wire in Comparative Example 2, which is an indicator of adhesion, was 0.25 N / mm. Also, when the flat wire was bent, lifting and wrinkling of the film were observed. Therefore, it was confirmed that the resin was not closely attached to the conductor, but was tightly attached to the conductor.
[0215] Example 1, Example 1'
[0216] The insulating film forming resin of Example 1 and Example 1' was the same resin as that of Comparative Example 2. The resin temperature at the die outlet during wire molding was set to 330°C, and a 200 μm extruded coating layer was formed. Here, the conductor temperature when the conductor came into contact with the resin was 350°C.
[0217] As an indicator of adhesion, the pull-out strength of the round wire in Example 1 is 14.0N, and the peel strength of the flat wire in Example 1' is 1.80N / mm. When the flat wire is bent, not only is no wrinkling of the film observed, but no floating is observed. Therefore, it can be confirmed that the adhesion of the resin to the conductor is independent of the shape of the conductor, and is higher than that of Comparative Example 1 and Comparative Example 1', respectively.
[0218] Embodiment 2, embodiment 2'
[0219] The insulating film forming resin of Example 2 and Example 2' was the same as that of Comparative Example 1 and Comparative Example 1'. The resin temperature at the die outlet during wire molding was set to 420°C, and a 200 μm extruded coating layer was formed. Here, the conductor temperature when the conductor contacted the resin was 450°C.
[0220] As an indicator of adhesion, the pull-out strength of the round wire in Example 2 is 20.0N, and the peel strength of the flat wire in Example 2' is 2.80N / mm. When the flat wire is bent, not only is no wrinkling of the film observed, but no floating is observed. Therefore, it can be confirmed that the adhesion of the resin to the conductor is independent of the shape of the conductor, and is higher than that of Example 1 and Example 1', respectively.
[0221] Embodiment 3, Embodiment 3'
[0222] The insulating film forming resin used in Examples 3 and 3' was a copolymer of tetrafluoroethylene and perfluoro(propyl vinyl ether) (PFA), with an MFR of 28 g / 10 minutes and a melting point of 303°C. In addition, the resin temperature at the die outlet during wire molding was set to 330°C, and an extruded coating layer of 140 μm was formed. Here, the conductor temperature when the conductor came into contact with the resin was 350°C.
[0223] As an indicator of adhesion, the pull-out strength of the round wire in Example 3 was 15.0 N, and the peel strength of the flat wire in Example 3' was 1.80 N / mm. During the bending process using the flat wire, neither wrinkles nor lifting of the film were observed.
[0224] Embodiment 4, embodiment 4'
[0225] The insulating film forming resin of Example 4 and Example 4' was the same resin as that of Comparative Example 1 and Comparative Example 1'. The resin temperature at the die outlet during wire molding was set to 350°C, and an extruded coating layer of 200 μm was formed. Here, the conductor temperature when the conductor came into contact with the resin was 400°C. In addition, the insulated wire of Example 4' was fired at 330°C for 2 minutes and at 350°C for 1 minute after molding.
[0226] As an indicator of adhesion, the peel strengths of the flat wires in Example 4 and Example 4' were 2.21 N / mm and 2.20 N / mm, respectively, and the adhesion was at the same level.
[0227] Example 5
[0228] The insulating film forming resin of Example 5 was the same resin as that of Example 3'. The resin temperature at the die outlet during wire molding was set to 310°C, and a 200 μm extruded coating layer was formed. Here, the conductor temperature when the conductor came into contact with the resin was 320°C.
[0229] The peel strength of the flat wire in Example 5, which is an indicator of adhesion, was 0.93 N / mm, and during the bending process using the flat wire, neither wrinkles nor lifting of the film were observed.
[0230] Example 6
[0231] The insulating film forming resin of Example 6 was the same resin as that of Comparative Example 2. The resin temperature at the die outlet during wire molding was set to 300°C, and a 200 μm extruded coating layer was formed. Here, the conductor temperature when the conductor came into contact with the resin was 320°C.
[0232] The peel strength of the flat wire in Example 6, which is an indicator of adhesion, was 1.00 N / mm, and during the bending process using the flat wire, neither wrinkles nor lifting of the film were observed.
[0233] Embodiment 7, Embodiment 7'
[0234] The insulating film forming resin of Example 7 was a copolymer of tetrafluoroethylene and perfluoro(propyl vinyl ether) (PFA), with an MFR of 2 g / 10 minutes and a melting point of 307°C. In addition, the resin temperature at the die outlet during wire molding was set to 424°C, and a 200 μm extruded coating layer was formed. Here, the conductor temperature when the conductor came into contact with the resin was 455°C.
[0235] As an indicator of adhesion, the pull-out strength of the round wire in Example 7 was 16.0 N, and the peel strength of the flat wire in Example 7' was 1.70 N / mm. During the bending process of the flat wire, neither wrinkles nor lifting of the film were observed, but melt fractures occurred on the surface of the wire, resulting in poor appearance.
[0236] Example 8
[0237] The insulating film forming resin of Example 8 is a copolymer of tetrafluoroethylene and perfluoro(propyl vinyl ether) (PFA), a resin having an MFR of 68 g / 10 minutes and a melting point of 295°C. The conductor of Example 8 has a surface roughness Sz of 7.72 μm. The resin temperature at the die outlet during wire molding is set to 360°C, and an extruded coating layer of 200 μm is formed. Here, the conductor temperature when the conductor contacts the resin is 400°C.
[0238] The peel strength of the flat wire in Example 8, which is an indicator of adhesion, was 3.50 N / mm, and during the bending process using the flat wire, neither wrinkles nor lifting of the film were observed.
[0239] Comparative Example 3, Comparative Example 3'
[0240] The insulating film forming resin of Comparative Examples 3 and 3' was the same resin as that of Comparative Examples 1 and 1'. The resin temperature at the die outlet during wire molding was set to 365°C, and an extruded coating layer of 200 μm was formed. Here, the conductor temperature at the die outlet was 260°C. In addition, the insulated wires of Comparative Examples 3 and 3' were fired at 330°C for 2 minutes and at 350°C for 1 minute after molding.
[0241] As an index of adhesion, the pull-out strength of the round wire in Comparative Example 3 was 3.0 N, and the peel strength of the flat wire in Comparative Example 3' was 0.001 N / mm, and the adhesion was at the same level as that in Comparative Example 1.
[0242] Comparative Example 4
[0243] The insulating film forming resin of Comparative Example 4 was the same resin as that of Comparative Example 1. The conductor of Comparative Example 4 was a conductor obtained by heating the conductor at 380°C and winding it. After the conductor was wound, the resin temperature at the die outlet during wire molding was set to 365°C, and the conductor temperature when the conductor and the resin were in contact was set to 260°C, as in Comparative Example 1, to form an extruded coating layer of 200 μm.
[0244] As an indicator of adhesion, the pull-out strength of the round wire in Comparative Example 4 was 3.0 N, and the adhesion force was at the same level as that of Comparative Example 1.
[0245] Embodiment 9, Embodiment 9'
[0246] The insulating film forming resin of Example 9 and Example 9' was the same as that of Comparative Example 1. The resin temperature at the die outlet during wire molding was set to 365°C, and extruded coating layers of 100 μm and 60 μm were formed, respectively. The conductor temperature when the conductor came into contact with the resin was 380°C.
[0247] As an index of adhesion, the pull-out strength of the round wire in Example 9 was 11.0 N, and the peel strength of the flat wire in Example 9' was 0.62 N / mm, which were higher than those of Comparative Examples 3' and 4.
[0248] Example 10
[0249] The insulating film forming resin of Example 10 was a terpolymer of tetrafluoroethylene, hexafluoropropylene and perfluoro(propyl vinyl ether), with an MFR of 6 g / 10 minutes and a melting point of 265°C. In addition, the resin temperature at the die outlet during wire molding was set to 300°C, and a 200 μm extruded coating layer was formed. Here, the conductor temperature when the conductor came into contact with the resin was 323°C.
[0250] The peel strength of the flat wire in Example 10, which is an indicator of adhesion, was 1.20 N / mm, but melt fracture occurred on the surface of the wire, resulting in poor appearance.
[0251] Embodiment 11
[0252] The insulating film forming resin of Example 11 was a copolymer of tetrafluoroethylene and hexafluoropropylene, with an MFR of 6 g / 10 minutes and a melting point of 270°C. In addition, the resin temperature at the die outlet during wire molding was set to 325°C, and a 200 μm extruded coating layer was formed. Here, the conductor temperature when the conductor came into contact with the resin was 350°C.
[0253] The pull-out strength of the round wire in Example 11, which is an indicator of adhesion, was 15.0N.
[0254] Tables 3 and 4 show the conditions and results of the electric wire molding.
[0255]
[0256]
Claims
1. An insulated wire comprising a conductor and a fluororesin layer formed on the conductor and containing a melt-processable fluororesin, wherein a peel strength measured by peeling the fluororesin layer from the conductor is 0.30 N / mm or more.
2. The insulated wire according to claim 1, wherein The cross-sectional shape of the conductor is approximately rectangular.
3. An insulated wire comprising a conductor and a fluororesin layer formed on the conductor and containing a melt-processable fluororesin, wherein a pull-out strength measured by pulling out the fluororesin from the conductor is 4N or more.
4. The insulated wire according to claim 3, wherein The cross-sectional shape of the conductor is approximately circular.
5. The insulated wire according to any one of claims 1 to 4, wherein The fluororesin layer is formed by extruding the fluororesin in a molten state onto the conductor heated to a temperature higher than the temperature of the fluororesin in a molten state.
6. The insulated wire according to any one of claims 1 to 5, wherein The conductor is composed of at least one selected from the group consisting of copper, copper alloys, aluminum, and aluminum alloys.
7. The insulated wire according to any one of claims 1 to 6, wherein The conductor has a surface roughness Sz of 0.2 μm to 12 μm.
8. The insulated wire according to any one of claims 1 to 7, wherein The thickness of the fluororesin layer is 40 μm to 300 μm.
9. The insulated wire according to any one of claims 1 to 8, wherein The relative dielectric constant of the fluororesin layer is 2.5 or less.
10. The insulated wire according to any one of claims 1 to 9, wherein The partial discharge inception voltage measured at 25°C satisfies the following relationship: Partial discharge inception voltage (V) ≥ 5.5 × t + 600 t: film thickness of the fluororesin layer, its unit is μm.
11. The insulated wire according to any one of claims 1 to 10, wherein The change rate calculated by the following formula is less than 10%, Change rate (%)=[(partial discharge inception voltage measured at 25° C.)−(partial discharge inception voltage measured at 200° C.)] / (partial discharge inception voltage measured at 25° C.)×100.
12. The insulated wire according to any one of claims 1 to 11, wherein The melt flow rate of the fluororesin is 0.1 g / 10 minutes to 120 g / 10 minutes.
13. The insulated wire according to any one of claims 1 to 12, wherein The melting point of the fluororesin is 240°C to 320°C.
14. The insulated wire according to any one of claims 1 to 13, wherein The fluororesin has a functional group, and the number of the functional groups of the fluororesin is relative to every 10 6 The number of carbon atoms ranges from 5 to 2000.
15. The insulated wire according to any one of claims 1 to 14, wherein The fluororesin contains tetrafluoroethylene units and fluoroalkyl vinyl ether units.
16. The insulated wire according to claim 15, wherein The content of the fluoroalkyl vinyl ether unit in the fluororesin is 1.0 mol% to 30.0 mol% based on the total monomer units.
17. The insulated wire according to any one of claims 1 to 14, wherein The fluororesin contains tetrafluoroethylene units and hexafluoropropylene units.
18. The insulated wire according to any one of claims 1 to 17, wherein The fluororesin has at least one functional group selected from the group consisting of a carbonyl-containing group, an amino group, a hydroxyl group, a -CF2H group, an olefin group, an epoxy group, and an isocyanate group.
19. A method for producing an insulated wire, the method comprising producing the insulated wire according to any one of claims 1 to 18 using an extrusion molding machine, wherein: The fluororesin is heated to melt the fluororesin, and the molten fluororesin is extruded onto a conductor heated to a temperature higher than the temperature of the molten fluororesin, thereby forming the fluororesin layer on the conductor.
20. The manufacturing method according to claim 19, wherein: The conductor is heated using a halogen heater.
Citation Information
Patent Citations
Fluorine-containing copolymer and its use
JP2006152234A
Insulated electric wire and its manufacturing method
JP2009245857A
Insulation wire and its manufacturing method
JP2014103045A
Insulated wire and method of manufacturing the same
JP2014154511A
Insulation wire and producing method thereof, and coil for electric device and producing method thereof
JP2015138626A